British literature, 1640-1789 : an anthology - 4 0 16; DeMaria, Robert; 5 (Malden, MA : Blackwell Pub., 2008)
An anthology of poems, short stories, essays, and other writings by various British authors from 1640 to 1789.
Includes bibliographical references (p. [1115]-1117) and indexes.
Adult;Adult
Keywords: 2 -- 0; 6; English literature;English literature;English literature;English literature -- 18th century.;Early modern, 1500-1700.;18th century.;16th and 17th centuries; Great Britain;Great Britain -- Literary collections.;Literary collections; 2